Ten years of eddy covariance measurements in Basel, Switzerland: Seasonal and interannual variabilities of urban CO2 mole fraction and flux. Issue 14 (19th July 2016) - Schmutz, M.; Vogt, R.; Feigenwinter, C.; Parlow, E.
Abstract: Eddy covariance (EC) measurements of carbon dioxide (CO2 ) in urban environments are carried out widely since the late nineties. However, long‐term time series are still rare and little is known about long‐term tendencies, even though cities are major sources of CO2 globally. Here a full decade of EC measurements from Basel, Switzerland, is presented. An approach for the calculation of horizontal averages is presented. It improves the significance and comparability of measured fluxes from heterogeneous environments and emphasizes the need of adequate weighting by horizontal averaging in such heterogeneous urban environments, especially for the derivation of cumulative quantities like the annual net ecosystem exchange. The urban CO2 mole fraction ( ρ C ) is compared with regional background measurements, and good agreement in terms of long‐term trend and seasonal variability is found. Over the last decade an increase of 2 ppm y −1 is observed, both locally and globally. CO2 flux ( F C ) data are analyzed for diurnal and seasonal cycles as well as interannual variabilities. F C shows a large interannual variability in times of high source activity (e.g., during the day and in winter). In contrast, a relatively constant background flux of 5 µmol m −2 s −1 is found during periods of low source activity. The long‐term trend of F C is mostly superimposed by the large temporal variability and is found to be −5% over the last 10 years. Key Points: Improved method of horizontal averaging for better comparability of flux data in heterogeneous environments presented Comparison of urban CO2 mole fraction to regional background records Long‐term (10 years) trends and variability of urban CO2 flux and mole fraction reported